2003
DOI: 10.1590/s0036-46652003000400003
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation on the gastrointestinal helminths of the Barbados green monkey, Cercopithecus aethiops sabaeus

Abstract: Faecal samples were collected from fifty three freshly captured monkeys which were kept at the Barbados Primate Research Centre and Wildlife Reserve (BPRCWR). Examination of these samples for gastrointestinal helminths using the zinc sulphate floatation method revealed an overall infection rate of 88.7%. The parasites observed included Strongyloides (62.4%), Physaloptera (58.5%), Trichuris (52.8%), Hookworm (34.0%), Oesophagostomum (30.2%), Trichostrongylus (3.8%) and Ascaris (5.7%). No significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 14 publications
4
17
3
Order By: Relevance
“…This result is similar to the earlier report of Corden et al (2008) and Opara et al (2010) who revealed 72.5% respectively 76.6% positive cases. Higher prevalences were found by Mutani et al (2003), who reported 88.7% postitive samples from Barbados. In contrary much lower prevalences were found by Stuart et al (1990), who only found 48% of the animals were infected with parasites in Costa Rica.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This result is similar to the earlier report of Corden et al (2008) and Opara et al (2010) who revealed 72.5% respectively 76.6% positive cases. Higher prevalences were found by Mutani et al (2003), who reported 88.7% postitive samples from Barbados. In contrary much lower prevalences were found by Stuart et al (1990), who only found 48% of the animals were infected with parasites in Costa Rica.…”
Section: Discussionmentioning
confidence: 81%
“…Trichuris sp. has often been recorded in primates (Mutani et al 2003;Kimberley et al 2004;Corden et al 2008;Lim et al 2008;Singh et al 2009) and Balantidium coli has been previously reported by Leveck et al (2007).…”
Section: Discussionmentioning
confidence: 90%
“…In this study, mixed infection was observed in twelve deer. The mixed infection in zoo animal was recorded by Kanungo et al (2010) and in monkeys by Mutani et al (2003) who commented that 58.5% of all monkeys examined had at least three parasite species and only 34.0% had between one and two parasite species. Seasonal prevalence of gastrointestinal parasites in deer at Char Kukri Mukri Seasonal fluctuation of the year had a significant (p<0.05) effect on the prevalence of gastrointestinal parasitic infection in deer.…”
Section: Prevalence Of Mixed Infection In Deer At Char Kukri Mukrimentioning
confidence: 84%
“…Mixed infection was observed in the fifteen animals such as butani cattle, giraffe, spotted deer, sambar deer, horse, greater kudu, nil gai, black wild beast, impala, hippopotamus, zebra, wild beast, one horned rhinoceros, common eland and oryx. Kanungo et al, (2010) and Mutani et al, (2003). This suggests that there is a fairly high rate of transmission of the parasites observed between individuals either because of the gregarious nature or because of suitable environmental conditions.…”
Section: Discussionmentioning
confidence: 97%